(untitled) (Revista Brasileira Multidisciplinar, 2022)
The objective of this work was to study the effectiveness of the implementation of the general law of micro and small companies (MPE), in the municipality of Barretos. The municipality regulated the General Law on Micro and Small Enterprises, through Municipal Complementary Law no. 84 of November 22, 2007, which started to regulate the right of MSEs to differentiated and favored treatment in relation to the others. Therefore, in order to investigate the proposed scope, the methodology used started by means of a bibliographic survey, then, the characterization of the municipality was carried out, through an analysis of the variables applied in the Municipal Development Index of Micro and Small Companies, the IDM-MPE, and, subsequently, the main public policy actions in support of MSEs were investigated, in order to verify what the municipality of Barretos has done to collaborate with its implementation. As a result, it was observed that the municipality did not implement public policy actions capable of promoting local development, with regard to access to credit, tax incentives, government purchases and entrepreneurial education. In the end, it was found that the general law on MSEs was not effective in the area, and the municipality should seek partnerships and more information capable of assisting it in this path to be followed.